A novel Stauntonia leucantha fruits arabinogalactan: and structural characterization. (1st March 2023) - Li, Hui; Gao, Tao; Zhang, Zhonghao; Lei, Jiangping; Hu, Junchao; Tang, Zizhong; Feng, Shiling; Ding, Chunbang; Chen, Tao; Chen, Yanger; Yuan, Shu; Yuan, Ming
Abstract: Polysaccharides were the key ingredients of many herbal medicines, and were responsible for multiple pharmacological activities. In this study, a novel polysaccharide fraction, named SLP-2, was isolated from Stauntonia leucantha fruits, and purified by DEAE-52 and Sephadex G-100 column chromatography. Furthermore, SLP-2 was identified by congo red, methylation, partial acid hydrolysis and NMR. The results indicated that the backbone of SLP-2 was composed of →4)-β-D-Gal p -(1 → 4)-β-D-Gal p -(1→ substituted at C-6 with 1, 5-linked arabinan. SLP-2 had good anti-oxidation ability in vitro. Surprisingly, we found that reduction of carboxyl groups and methylation of hydroxyl groups enhanced the ability to scavenge 2, 2′-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radicals and inhibit lipid peroxidation, and weakened the activity to scavenge 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radicals and reduce ferric iron. Graphical abstract: Unlabelled Image Highlights: An arabinogalactan (SLP-2) was isolated from wild fruits of Stauntonia leucantha . SLP-2 composed of a galactose backbone and arabinose branches. The antioxidant activity of SLP-2 largely depended on carboxyl and hydroxyl groups.